Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

HEL ASAP
Solve for x.
2(3x + 4) = 7x – 2x + 1


Sagot :

Answer:

x= -7

Step-by-step explanation:

[tex]~~~~~~2(3x+4) = 7x-2x+1\\\\\implies 6x +8 = 5x+1\\\\\implies 6x -5x = 1-8\\\\\implies x = -7[/tex]